Teacher ethics in wisdom-based educational innovation: a cross-cultural analysis - Endang Wuryandini; Gildan Jaya Muhammad Ramadhan; Achmad Agung (Indonesian Institute For Counseling, Education and Therapy, 2026)
This integrative review examines how teacher ethics shapes the implementation of local wisdom-based educational innovation in Indonesian education. Local wisdom-based educational innovation is operationalized as the deliberate integration of locally rooted cultural knowledge, values, languages, social practices, and ecological understandings into curriculum, pedagogy, learning media, assessment, school culture, or school-community collaboration, subject to ethical principles of justice, care, inclusiveness, and respect for human dignity. Sources were identified and bibliographically verified through ERIC, DOAJ, Crossref-linked publisher records, journal platforms, and official Indonesian policy repositories using Boolean combinations of